Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Cotton mitogen-activated protein kinase4 (GhMPK4) confers the transgenic Arabidopsis hypersensitivity to salt and osmotic stresses - Na-Na Wang; Li–Li Zhao; Rui Lu; Yang Li; Xue-Bao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Hydrolysis and volatile fatty acids accumulation of waste activated sludge enhanced by the combined use of nitrite and alkaline pH - Cheng Huang; Congcong Liu; Xiuyun Sun; Yinglu Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Xiaodong Liu; Lianjun Wang (Environmental Science and Pollution Research, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Response difference of transgenic and conventional rice (Oryza sativa) to nanoparticles (γFe2O3) - Xin Gui; Yingqing Deng; Yukui Rui; Binbin Gao; Wenhe Luo; Shili Chen; Le Van Nhan; Xuguang Li; Shutong Liu; Yaning Han; Liming Liu; Baoshan Xing (Environmental Science and Pollution Research, 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Changes in photosynthesis of alpine plant Saussurea superba during leaf expansion - Sheng-Bo Shi; Rui Shi; Miao Li (Acta Physiologiae Plantarum, 2015)

Effect of hydrogen sulfide on D1 protein in wheat under drought stress - Hua Li; Ming Quan Gao; Rui Li Xue; Dan Wang; Hui Jie Zhao (Acta Physiologiae Plantarum, 2015)

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

Combined drought and heat stress in Camellia oleifera cultivars: leaf characteristics, soluble sugar and protein contents, and Rubisco gene expression - Baoming Wang; Jianjun Chen; Longsheng Chen; Xiangnan Wang; Rui Wang; Li Ma; Shaofeng Peng; Jian Luo; Yongzhong Chen (Trees, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)

The processes of graft union formation in tomato - Jingwei Fan; Rui Yang; Xiaoman Li; Wenchao Zhao; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2015)

Meiothermus roseus sp. nov., a thermophilic bacterium isolated from a geothermal area - Hong Ming; Yan-Yan Duan; Qian-Qian Guo; Yi-Rui Yin; En-Min Zhou; Lan Liu; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

EMD Method Applied to Identification of Logging Sequence Strata - Ni Zhao; Rui Li (Acta Geophysica, 2015)

Atrokylindriopsis, a new genus of hyphomycetes from Hainan, China, with relationship to Chaetothyriales - Ying-Rui Ma; Ji-Wen Xia; Jian-Mei Gao; Xiang-Yu Li; Rafael F. Castañeda Ruíz; Xiu-Guo Zhang; Zhuang Li (Mycological Progress, 2015)

Anti-inflammatory effect of procyanidin B1 on LPS-treated THP1 cells via interaction with the TLR4–MD-2 heterodimer and p38 MAPK and NF-κB signaling - Jing Xing; Rui Li; Nan Li; Jian Zhang; Yueqing Li; Ping Gong; Dongna Gao; Hui Liu; Yu Zhang (Molecular and Cellular Biochemistry, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Erratum to: Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Predicting Inter-session Performance of SMR-Based Brain–Computer Interface Using the Spectral Entropy of Resting-State EEG - Rui Zhang; Peng Xu; Rui Chen; Fali Li; Lanjin Guo; Peiyang Li; Tao Zhang; Dezhong Yao (Brain Topography, 2015)

Effect of mowing on N2O and CH4 fluxes emissions from the meadow-steppe grasslands of Inner Mongolia - Zedong Lu; Rui Du; Pengrui Du; Ziming Li; Zongmin Liang; Yaling Wang; Saisai Qin; Lei Zhong (Frontiers of Earth Science, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Novosphingobium endophyticum sp. nov. isolated from roots of Glycyrrhiza uralensis - Yan-Qiong Li; Li Li; Wei Chen; Yan-Qing Duan; Salam Nimaichand; Jian-Wei Guo; Rui Gao; Wen-Jun Li (Archives of Microbiology, 2015)

Umezawaea endophytica sp. nov., isolated from tobacco root samples - Xiao Chu; Bing-Bing Liu; Rui Gao; Zheng-Yu Zhang; Yan-Qing Duan; Salam Nimaichand; Wei Chen; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Characterization of Soybean mosaic virus resistance derived from inverted repeat-SMV-HC-Pro genes in multiple soybean cultivars - Le Gao; Xueni Ding; Kai Li; Wenlin Liao; Yongkun Zhong; Rui Ren; Zhitao Liu; Karthikeyan Adhimoolam; Haijian Zhi (Theoretical and Applied Genetics, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Prioritizing Genes Related to Nicotine Addiction Via a Multi-source-Based Approach - Xinhua Liu; Meng Liu; Xia Li; Lihua Zhang; Rui Fan; Ju Wang (Molecular Neurobiology, 2015)

Attenuated Blood-Brain Barrier Dysfunction by XQ-1H Following Ischemic Stroke in Hyperlipidemic Rats - Weirong Fang; Lan Sha; Nandani Darshika Kodithuwakku; Jie Wei; Rui Zhang; Dan Han; Lishun Mao; Yunman Li (Molecular Neurobiology, 2015)

Mertk deficiency alters expression of micrornas in the retinal pigment epithelium cells - Yong Tang; Qingjun Lu; Yunrong Wei; Lixia Han; Rui Ji; Qiutang Li; Qingxian Lu (Metabolic Brain Disease, 2015)

Numerical Simulation of Coronary Artery Stenosis Before and After Stenting - Gang Li; Rui Hu; Feng Gao (Journal of Medical and Biological Engineering, 2015)

Protective enzymes and genes related to the JA pathway are involved in the response to root-knot nematodes at high soil temperatures in tomatoes carrying Mi-1 - Canli Hu; Wenchao Zhao; Jingwei Fan; Zilong Li; Rui Yang; Fukuan Zhao; JianLi Wang; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2015)

Activin A can induce definitive endoderm differentiation from human parthenogenetic embryonic stem cells - Zhiqiang Wang; Wenliang Li; Tianxing Chen; Jun Yang; Zhengqi Wen; Xinmin Yan; Tao Shen; Rui Liang (Biotechnology Letters, 2015)

Changes in global DNA methylation intensity and DNMT1 transcription during the aging process of scallop Chlamys farreri - Shanshan Lian; Yan He; Xue Li; Bosong Zhao; Rui Hou; Xiaoli Hu; Lingling Zhang; Zhenmin Bao (Journal of Ocean University of China, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

Detecting 2014 Northern Iraq Insurgency using night-time light imagery - Xi Li; Rui Zhang; Chengquan Huang; Deren Li (International Journal of Remote Sensing, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Diagnosis of Small Bowel Obstruction using Targeted Enterography During Nasointestinal Decompression - Rui-hong Li; De-chun Li; Qin-zhong Tian; Ping Wu; Xin-hui Zhang (Cell Biochemistry and Biophysics, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

The concentration of selenium matters: a field study on mercury accumulation in rice by selenite treatment in qingzhen, Guizhou, China - Yu-Feng Li; Jiating Zhao; Yunyun Li; Hanjun Li; Junfang Zhang; Bai Li; Yuxi Gao; Chunying Chen; Manyi Luo; Rui Huang; Jun Li (Plant and Soil, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Evaluation of miRNA-binding-site SNPs of MRE11A, NBS1, RAD51 and RAD52 involved in HRR pathway genes and risk of breast cancer in China - Zhenzhen Wu; Peng Wang; Chunhua Song; Kaijuan Wang; Rui Yan; Jingruo Li; Liping Dai (Molecular Genetics and Genomics, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

TAM receptor deficiency affects adult hippocampal neurogenesis - Rui Ji; Lingbin Meng; Qiutang Li; Qingxian Lu (Metabolic Brain Disease, 2015)

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Ribosomal Protein L3 Mutations are Associated with cfr-Mediated Linezolid Resistance in Clinical Isolates of Staphylococcus cohnii - Hongtao Xu; Rui Tian; Yanming Li; Dongke Chen; Yalin Liu; Yunjian Hu; Fei Xiao (Current Microbiology, 2015)

Radiophotographically Controlled Nasointestinal Intubation to Treat Recurrent Postoperative Adhesive Ileus - Rui-hong Li; De-chun Li; Xiao-peng Lv; Bin Quan (Cell Biochemistry and Biophysics, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Characterization of genomic sequence of a drought-resistant gene TaSnRK2.7 in wheat species - HONG YING ZHANG; WEI LI; XIN GUO MAO; RUI LIAN JING (Journal of Genetics, 2015)

Mineralogy and isotope geochemical characteristics for Xiaozhen copper deposit, Langao County, Shaanxi Province and their constraint on genesis of the deposit - Gang Wang; Zong-qi Wang; Rui Shi; Ying-li Zhang; Kun-ming Wang (Geosciences Journal, 2015)

Marinactinospora endophytica sp. nov., isolated from a medicinal plant - Min-Jiao Liu; Thi-Nhan Khieu; Rui Gao; Wael N. Hozzein; Hong-Fei Wang; Wei Yang; Salam Nimaichand; Zhi Xiong; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

Vegetation physiological parameter setting in the Simple Biosphere model 2 (SiB2) for alpine meadows in the upper reaches of Heihe river - Yuan Li; Rui Sun; ShaoMin Liu (Science China Earth Sciences, 2015)

Comparative genomic approach reveals novel conserved microRNAs in Inner Mongolia cashmere goat skin and longissimus dorsi - Rui Su; Shaoyin Fu; Yanjun Zhang; Ruijun Wang; Yanhong Zhou; Jinquan Li; Wenguang Zhang (Molecular Biology Reports, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

A Controlled Study of Alprostadil Liposomal Preparation in the Treatment of Blue Toe Syndrome - Hai-lin Xi; Rui Li; Zhi-long Tian; Su Feng; Gao-Lei Jia (Cell Biochemistry and Biophysics, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

Cloning and expression analysis of phenylalanine ammonia-lyase (PAL) gene family and cinnamate 4-hydroxylase (C4H) from Dryopteris fragrans - Yan Li; Lili Sun; Hemeng Wang; Rui Gao; Junzheng Zhang; Baozhong Hu; Ying Chang (Biologia, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Genome-Wide Identification, Expression, and Activity Analysis of Alkaline/Neutral Invertase Gene Family from Cassava (Manihot esculenta Crantz) - Yuan Yao; Meng-Ting Geng; Xiao-Hui Wu; Jiao Liu; Rui-Mei Li; Xin-Wen Hu; Jian-Chun Guo (Plant Molecular Biology Reporter, 2015)

Bencycloquidium bromide inhibits nasal hypersecretion in a rat model of allergic rhinitis - Rui Long; Yuanda Zhou; Jiangju Huang; Li Peng; Long Meng; Shenyin Zhu; Juan Li (Inflammation Research, 2015)

Low Bone Mass is Associated with Stroke in Chinese Postmenopausal Women: The Chongqing Osteoporosis Study - Rui Zhou; Dong Liu; Rui Li; Shiming Zhou; Min Cui; Lin Chen; Huadong Zhou (Cell Biochemistry and Biophysics, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Isolation and in silico characterization of a shikimate kinase from Cassia obtusifolia - Zubi Liu; Qiankun Zhu; Yangyang Li; Jihua Yu; Wanjun Wang; Rui Tan; Jiayu Zhou; Hai Liao (Acta Physiologiae Plantarum, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Isolation, Characterization and Promoter Analysis of Cell Wall Invertase Gene SoCIN1 from Sugarcane (Saccharum spp.) - Jun-Qi Niu; Ai-Qin Wang; Jing-Li Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Effect of Drought Stress on Anatomical Structure and Chloroplast Ultrastructure in Leaves of Sugarcane - Feng-Juan Zhang; Kun-Kun Zhang; Cheng-Zhong Du; Jian Li; Yong-Xiu Xing; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Research and Development Priorities for Sugar Industry of China: Recent Research Highlights - Yang-Rui Li; Li-Tao Yang (Sugar Tech, 2015)

Sugarcane Agriculture and Sugar Industry in China - Yang-Rui Li; Li-Tao Yang (Sugar Tech, 2015)

Physiological and Biochemical Characteristics Related to Cold Resistance in Sugarcane - Bao-Qing Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Effects of Exogenous Abscisic Acid on Cell Membrane and Endogenous Hormone Contents in Leaves of Sugarcane Seedlings under Cold Stress - Xing Huang; Ming-Hui Chen; Li-Tao Yang; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Increased Expression of Protease-Activated Receptor 2 and 4 Within Dorsal Root Ganglia in a Rat Model of Bone Cancer Pain - Yanju Bao; Wei Hou; Liping Yang; Rui Liu; Yebo Gao; Xiangying Kong; Zhan Shi; Weidong Li; Honggang Zheng; Shulong Jiang; Baojin Hua (Journal of Molecular Neuroscience, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Recent climate warming of central China reflected by temperature-sensitive tree growth in the eastern Qinling Mountains and its linkages to the Pacific and Atlantic oceans - Feng Chen; Rui-bo Zhang; Hui-qin Wang; Li Qin (Journal of Mountain Science, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

The Influence of Land Use on the Abundance and Diversity of Ammonia Oxidizers - Dayong Zhao; Juan Luo; Jianqun Wang; Rui Huang; Kun Guo; Yi Li; Qinglong L. Wu (Current Microbiology, 2015)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Numerical study of the secondary circulations in rip current systems - Rui Li; Changlong Guan (Journal of Ocean University of China, 2015)

Chemical modification, characterization and bioactivity of a released exopolysaccharide (r-EPS1) from Lactobacillus plantarum 70810 - Kun Wang; Wei Li; Xin Rui; Teng Li; Xiaohong Chen; Mei Jiang; Mingsheng Dong (Glycoconjugate Journal, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

LSM14A inhibits porcine reproductive and respiratory syndrome virus (PRRSV) replication by activating IFN-β signaling pathway in Marc-145 - Zhenhong Li; Rui Chen; Jinhua Zhao; Ziyu Qi; Likai Ji; Yueran Zhen; Bang Liu (Molecular and Cellular Biochemistry, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Contribution weight of engineering technology on pollutant emission reduction based on IPAT and LMDI methods - Hairti Tursun; Zhenyang Li; Rui Liu; Yuan Li; Xiaohui Wang (Clean Technologies and Environmental Policy, 2015)

H2O2 Induces Myocardial Hypertrophy in H9c2 Cells: A Potential Role of Ube3a - Rui Song; Jie Zhang; Lijuan Zhang; Guanghua Wang; Da Wo; Jian Feng; Xucheng Li; Jue Li (Cardiovascular Toxicology, 2015)

Potential impact of climate change on future water demand in Yulin city, Northwest China - Wang Xiao-jun; Zhang Jian-yun; Shahid Shamsuddin; He Rui-min; Xia Xing-hui; Mou Xin-li (Mitigation and Adaptation Strategies for Global Change, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Composition and variation analysis of TCR β-chain CDR3 repertoire in the thymus and spleen of MRL/lpr mouse at different ages - Zhou Li; Ma Long; Liu ChunMei; Shi Bin; Yu Jiang; Ma Rui; Ma Qingqing; Yao XinSheng (Immunogenetics, 2015)

An 18-element GEO broadcast ephemeris based on non-singular elements - Lan Du; Zhongkai Zhang; Jin Zhang; Li Liu; Rui Guo; Feng He (GPS Solutions, 2015)